(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2013)
Kutai vernacular houses represent Kutai tradition in East Kalimantan. Kutai Vernacular Houses are spread over Kabupaten Kutai Kartanegara (Kukar). It is closely related to the culture of majority in Kukar. The locus of the research is Tenggarong, a sub-district of Kukar. Kukar now faces flood due to rainy season. Both climate change and environmental impact raise the water level, but Kutai vernacular houses are still exist. How the Kutai vernacular houses addapt in flood zone is the aim of the research. The research method is analyzing the changes of structure and construction of Kutai Vernacular Houses, from the beginning of the house built to the latest condition. The conclusion: there are some long lasting adaptation while others are newer adjustments in order to keep Kutai Vernacular Houses survived.